Transformacija turistične infrastrukture in obiska v Mariboru v zadnjih dveh desetletjih - Horvat, Uroš (Journal for Geography, 2012)
The paper presents the development of tourism in Maribor, with a focus on major changes in the tourist offer (especially tourist infrastructure and accommodation facilities) and tourist visit since 1991. Changes in tourist flows to South-East Europe, the great economic crises and the collapse of the major industrial companies in Maribor was followed by a large decrease in tourist visit and the need for transformation of the tourist offer in the city. In Maribor was built a range of new hotels and other accommodation facilities, which resulted in the fact that since 2000 increased diversity and quality of the tourist offer and, consequently, has gradually started to increase also the tourist visit. However, Maribor still shows all the characteristics of a tourist destination with the dominant urban tourism, which is characterized by short average length of stay of tourists and the high share of overnight stays in hotels.
Keywords: tourism; urban tourism; tourist visit; tourist infrastructure; Maribor; Slovenia